Crystalline phase effect on the up-conversion processes and white emission of Yb3+/Er3+/Tm3+:Y2Si2O7 nanocrystals - ERDEM, MURAT; SAMUR, RAMAZAN (ROYAL SOC CHEMISTRY, 2019)
Yb3+,Er3+,Tm3+:Y2Si2O7 nanopowders were fabricated by a sol-gel method and then annealed at two different temperatures of 1050 degrees C and 1480 degrees C for 12 h to investigate the phase effect on the structural and optical properties. X-ray diffraction patterns (XRD) of all powders revealed that most of the peaks were in good harmony with the standard JCPDS cards of Y2Si2O7 (PDF #38-0223 and PDF #38-0440). SEM images of the powders were taken to examine the morphology and chemical composition of the powders. Diffuse reflection spectra of Y2Si2O7 exhibited varying number of transitions depending on the dopant ion in all powders in the range of 400-1050 nm. The spectral properties of the powders were investigated to identify the possible up-conversion (UC) emission mechanism in the range between 400 and 900 nm under 975 nm excitation. A broadening white light emission was observed with increasing laser pumping power at room temperature as well. Spectral profiles of the transitions observed in both reflectance and up-conversion luminescence spectra were found to be crystalline phase dependent.
Keywords: LIGHT EMISSION; YB3+; LUMINESCENCE; ER3+